(untitled) (Journal of Organizational Psychology, 2020)
The mining industry has played a significant role in the development of South Africa by being a top employer and foreign exchange earner. With the large workforce, labour unions have also emerged as an important factor that moderates how people, companies, and the government interact. In recent years, union-led mass actions have been on the limelight due to their violent nature that endangers human life, the reputation of the stakeholders, and compromises the economic contributions of the mining sector. The intent of this research was to investigate the impact of the labour unions on the mining industry in South Africa.